The bioeconomy transformation as an external enabler of sustainable entrepreneurship - Sebastian Hinderer; Andreas Kuckertz (Business Strategy and the Environment, 2022)
Bioeconomy strategies worldwide emphasize the importance of entrepreneurship in the transformation toward a sustainable and circular bioeconomy. However, the bioeconomy transformation itself also offers great opportunities for creating new ventures. Based on interviews with bioeconomy entrepreneurs from six European countries, we investigate how entrepreneurial opportunities emerge in the bioeconomy context and what competencies entrepreneurs need to act on them. By conceptualizing the bioeconomy transformation as an external enabler of entrepreneurial activity, we open new avenues for research on sustainable development and innovation policy. We conceptualize sustainable entrepreneurship as a phenomenon that can be enabled externally via the transformation toward sustainable development. Furthermore, we show that new venture creation in the bioeconomy requires unique knowledge (transformative knowledge) and specific competencies (sustainable valorization of biomass, marketing of biobased products, and management of limited resources).
Keywords: 330; bioeconomy; competencies; external enablement; sustainable development; sustainable entrepreneurship; sustainable innovation policy